Богатыри - Княжевич Александр (Прикольный детектив, 2018)
Экземпляры: ДБ (20180906) / Инвентарный номер: 50436 / Цена: 250.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: К 54 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6